Pengaruh Lingkungan Sekolah terhadap Hasil Belajar Siswa Sekolah Menengah Pertama - Mohammad Fajar Shodiq; Didit Darmawan (IHSANIKA : Jurnal Pendidikan Agama Islam, 2025)
The school environment is one of the important factors that affect the student learning process. This study aims to analyze the influence of the school environment on the quality of student learning. The school environment includes the physical, social, and psychological conditions that students face while at school. Factors such as learning facilities, classroom atmosphere, interaction with teachers, relationships with peers, and emotional support from school residents have a significant role in motivating and improving student achievement. The results of the study show that a positive and conducive school environment can increase student motivation, concentration, and academic achievement. On the other hand, a less supportive environment can hinder academic development and decrease students' interest in learning. Therefore, it is important for schools to create a learning environment that is comfortable, supportive, and encourages students to achieve optimal results in learning.